2011
DOI: 10.1021/la2038262
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Sand via Adsorption of Cationic Moringa oleifera Protein

Abstract: Moringa oleifera (Moringa) seeds contain a natural cationic protein (MOCP) that can be used as an antimicrobial flocculant for water clarification. Currently, the main barrier to using Moringa seeds for producing potable water is that the seeds release other water-soluble proteins and organic matter, which increase the concentration of dissolved organic matter (DOM) in the water. The presence of this DOM supports the regrowth of pathogens in treated water, preventing its storage and later use. A new strategy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 21 publications
3
44
0
3
Order By: Relevance
“…A modified method described in [13] was used to functionalize the three adsorbents with MOPE. MO solutions at concentrations ranging from 0.25 to 1.7 mg/ml were prepared by dissolving crushed MO seeds in deionized water and then shaking the solution continuously for 1 hour at room temperature.…”
Section: Batch Protein Sorption Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified method described in [13] was used to functionalize the three adsorbents with MOPE. MO solutions at concentrations ranging from 0.25 to 1.7 mg/ml were prepared by dissolving crushed MO seeds in deionized water and then shaking the solution continuously for 1 hour at room temperature.…”
Section: Batch Protein Sorption Experimentsmentioning
confidence: 99%
“…The bacterial solution was diluted in phosphate buffer solution according to a procedure described in [13], to a final concentration of 10 3 -10 5 CFU/ml. Duplicates of 1 g each of sand, burnt rice husk, and activated carbon were incubated with MOPE and were washed vigorously to remove excess MOPE extract prior to the bacterial experiments.…”
Section: Batch E Coli Experimentsmentioning
confidence: 99%
“…The flocculating cationic polypeptide is another antimicrobial peptide isolated from the seed of Moringa oleifera and also referred as Flo or MOCP [21][22][23]. The flocculation cationic polypeptide showed antibacterial activity by damaging bacterial cell membranes and causing fusion between membranes.…”
Section: Antibacterial Activities Of Moringa Oleiferamentioning
confidence: 99%
“…Grzesiak et al reported remediation of heavy metals from soil using quartz sand functionalized with organic amino silanes . There are also few articles on the antimicrobial sand particles prepared via surface modification, for example, with N ‐halamine acrylamidesiloxane copolymer, and cationic Moringa oleifera protein . Little attention however, has been paid to the application of functionalized sand as catalyst.…”
Section: Introductionmentioning
confidence: 99%